Quantifying B-cell Clonal Diversity In Repertoire Data - Pelissier, Aurelien; Luo, Siyuan; Stratigopoulou, Maria; Guikema, Jeroen; Maria Rodriguez Martinez (bioRxiv, 2022)
The adaptive immune system has the extraordinary ability to produce a broad range of immunoglobulins that can bind a wide variety of antigens. During adaptive immune responses, activated B~cells proliferate and undergo somatic hypermutation in their B-cell receptor (BCR) genes, resulting in clonal groups of diversified B~cells that can be related back to a common ancestor. Advances in high-throughput sequencing technologies have enabled the high-throughput characterization of B-cell receptor sequencing data, however, the accurate identification of clonally related BCR sequences remains a major challenge. In this study, we compare three different clone identification methods on both simulated and experimental data, and investigate their impact on the characterization of B-cell diversity. We find that different methods may lead to different clonal definitions, which in turn can affect the quantification of clonal diversity in repertoire data. Interestingly, we find the Shannon entropy to be overall the most robust diversity index in regard to different clonal identification. Our analysis also suggests that the traditional germline gene alignment-based method for clonal identification remains the most accurate when the complete information about the sequence is known, but that alignment-free methods may be preferred for shorter read length. We make our implementation freely available as a Python library cdiversity.Competing Interest StatementThe authors have declared no competing interest.Footnotes* added references